The Effect of Financial Literacy and Risk Perception on Pay Later Usage Decision by Gen Z - Shafira Salsabilah; Dea Amanda Adi Saputri; Acep Komara (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to examine how risk perception and financial literacy influence Generation Z's choice to adopt the Pay Later payment method in Cirebon City. Although Pay Later service is a Financial Technology (Fintech) innovation becoming increasingly popular among young people, it also contains financial hazards if used carelessly. In this study, 156 members of Generation Z who have utilized Pay Later services participated in a quantitative study using a Partial Least Square (PLS) approach. The research findings show that the decision to choose a Pay Later payment plan is positively and significantly influenced by risk perception and financial literacy. High risk perception encourages caution in financial decision-making, although good financial literacy makes people more selective in the use of this service. Combined, these two factors can explain the difference in the choice to use Pay Later. These results highlight the importance of improving risk transparency and financial education when using digital financial services, especially for younger people.